Análisis de la sentencia número 878-20-JP/24: Impacto y efectos de aplicación en el Código del Trabajo - Quizhpe Gualán, Kerly Yadira (2024)
This curricular integration work focuses on a doctrinal legal analysis of the Ecuadorian legislation that regulates the maternity rights of female workers, with emphasis on the sentence 878-20-JP/24 of the Constitutional Court of Ecuador. The research analyzes the applicable legislation in both the public and private sectors identifying the differences and areas for improvement in the protection of the rights of female workers during maternity periods. The current regulations in Ecuador are studied, highlighting the laws governing maternity leave and contrasting them with those established by the International Labor Organization (ILO). Through the analysis of sentence 878-20-JP/24, it is understood the impact of the judicial decision on the application of the regulations and on the equity between the labor sectors. The research, based on a qualitative methodology that includes legal review, interviews with professionals in the legal and human resources field, as well as surveys of female workers, to obtain a comprehensive perspective on the implementation and effectiveness of maternity policies in Ecuador. The result was that, despite progress, inequalities persist in the application of maternity rights. The study concludes with recommendations for aligning Ecuadorian regulations with international standards, with the aim of guaranteeing comprehensive and equitable protection for all female workers in Ecuador.